 Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

# The n-Pythagorean Fuzzy Sets

Department of Computer Science, Opole University of Technology, Proszkowska 76, 45-758 Opole, Poland
Symmetry 2020, 12(11), 1772; https://doi.org/10.3390/sym12111772
Received: 16 September 2020 / Revised: 22 October 2020 / Accepted: 23 October 2020 / Published: 26 October 2020
(This article belongs to the Special Issue Theoretical Computer Science and Discrete Mathematics)

## Abstract

:
The following paper presents deductive theories of n-Pythagorean fuzzy sets (n-PFS). N-PFS objects are a generalization of the intuitionistic fuzzy sets (IFSs) and the Yager Pythagorean fuzzy sets (PFSs). Until now, the values of membership and non-membership functions have been described on a one-to-one scale and a quadratic function scale. There is a symmetry between the values of this membership and non-membership functions. The scales of any power functions are used here in order to increase the scope of the decision-making problems. The theory of n-PFS introduces a conceptual apparatus analogous to the classic theory of Zadeh fuzzy sets, consistently striving to correctly define the n-PFS algebra.

## 1. Introduction

Zadeh  introduced the fuzzy set idea, which generalizes the theory of classical sets. In fuzzy sets, there is a membership function $μ$, which assigns a number from the set $[ 0 , 1 ]$ to each element of the universe. This determines how much this element belongs to this universe, where 0 means no belonging and 1 means full belonging to the set that is under consideration. Other values between 0 and 1 mean the degree of belonging to this set. This membership function is defined to describe the degree of belonging of an element to some class. The membership function in the fuzzy sets replace the characteristic function that is used in crisp sets. Since the work of Zadeh, the fuzzy set theory has been used in different disciplines such as management sciences, engineering, mathematics, social sciences, statistics, signal processing, artificial intelligence, automata theory, and medical and life sciences.
Atanassov studied the intuitionistic fuzzy sets (IFSs) [2,3]. IFSs have values for two functions: the membership function $μ$ and the non-membership function v. Additionally, there is a constraint $0 ≤ μ + v ≤ 1$. This is a symmetric relationship between the values and the membership function. In order to create model for imprecise information, the model of Pythagorean fuzzy sets (PFSs) was proposed by Yager [4,5]. This model is different than the IFSs model because it uses the condition $0 ≤ μ 2 + v 2 ≤ 1$. Moreover, there is also the Pythagorean fuzzy number (PFN) idea established by Zhang and Xu . In decision-making problems, there are also applications of PFSs proposed by Garg [7,8].
The decision-making problems in the model of Pythagorean fuzzy sets will significantly increase the application range of solving these problems than in the model of intuitionistic fuzzy sets. It is because more pairs $( μ , v )$ satisfy the condition $0 ≤ μ 2 + v 2 ≤ 1$ than the condition $0 ≤ μ + v ≤ 1$. Is there any other data scale in decision-making problems that will help to extend its applicability even further? Yes, with the condition $0 ≤ μ n + v n ≤ 1$, for any natural number $n > 2$.
In articles using local deduction regarding IFSs [3,9,10,11,12] and concerning PFSs [4,5,13,14,15,16,17], it was noted that there is a series of mathematical and logical inaccuracies. That is why the conceptual apparatus should be generalized and refined by formulating the deductive theory of n-Pythagorean fuzzy sets with the condition $0 ≤ μ n + v n ≤ 1$, for any natural number $n 〉 0$. The theory is presented below.

## 2. Triangular Norms

Definition 1.
The operation $• t : [ 0 , 1 ] × [ 0 , 1 ] → [ 0 , 1 ]$ is called a t-norm in the set $[ 0 , 1 ]$, or a triangular norm, when it meets the following conditions (for any numbers $x , y , z ∈ [ 0 , 1 ]$):
1.
boundary conditions
$0 • t y = 0 , y • t 1 = y ,$
2.
monotonicity
$x • t y ≤ z • t y , w h e n x ≤ z ,$
3.
commutativity
$x • t y = y • t x ,$
4.
associativity
$x • t ( y • t z ) = ( x • t y ) • t z ,$
Since there is $sup { t ∈ [ 0 , 1 ] : x • t t ≤ y }$, there can be specified the operation $→ t : [ 0 , 1 ] × [ 0 , 1 ] → [ 0 , 1 ]$, such that for any numbers $x , y ∈ [ 0 , 1 ]$:
$x → t y = sup { t ∈ [ 0 , 1 ] : x • t t ≤ y } .$
This operation is called t-residuum in the set $[ 0 , 1 ]$.
The operation $• s : [ 0 , 1 ] × [ 0 , 1 ] → [ 0 , 1 ]$, described by formula for any numbers $x , y ∈ [ 0 , 1 ]$:
$x • s y = 1 − ( 1 − x ) • t ( 1 − y ) ,$
is called a s-norm or triangular conorm.
Using the definitions of t-norm and s-norm, after simple calculations we get (where the names of conditions are given analogously to the definition of t-norm):
Theorem 1.
For any numbers $x , y , z ∈ [ 0 , 1 ]$:
• boundary conditions
$0 • s y = y , y • s 1 = 1 ,$
• monotonicity
$x • s y ≤ z • s y , w h e n x ≤ z ,$
• commutativity
$x • s y = y • s x ,$
• associativity
$x • s ( y • s z ) = ( x • s y ) • s z ,$
Further, only continuous t-norms and s-norms are considered. The general discussion on the construction of triangular norms, using the results of functional equations, leads to the theorem from paper :
Theorem 2.
1.
There is a continuous and strictly decreasing function for each continuous t-norm $f t : [ 0 , 1 ] → [ 0 , + ∞ )$ such that $f t ( 1 ) = 0 , f t ( 0 ) = 1$ and for any $x , y ∈ [ 0 , 1 ]$:
$x • t y = f t − 1 [ f t ( x ) + f t ( y ) ] , f t ( x ) + f t ( y ) ∈ [ 0 , 1 ] 0 , otherwise .$
2.
There is a continuous and strictly increasing function for each continuous s-norm $f s : [ 0 , 1 ] → [ 0 , + ∞ )$ such that $f s ( 0 ) = 0 , f s ( 1 ) = 1$ and for any $x , y ∈ [ 0 , 1 ]$:
$x • s y = f s − 1 [ f s ( x ) + f s ( y ) ] , f s ( x ) + f s ( y ) ∈ [ 0 , 1 ] 1 , otherwise .$
3.
For any $x ∈ [ 0 , 1 ]$
$f s ( x ) = f t ( 1 − x ) .$
Functions $f t , f s$ are called generators of t-norm and s-norm, respectively.
Example 1.
For the t-norm $x • t y = min { x , y }$ and any $x , y ∈ [ 0 , 1 ]$, the generator is $f t ( x ) = 1 − x$.
For the s-norm $x • s y = max { x , y }$ and any $x , y ∈ [ 0 , 1 ]$, the generator is $f s ( x ) = x$.
Example 2.
For the t-norm $x • t y = 1 − min { 1 , ( ( 1 − x ) p + ( 1 − y ) p ) 1 / p } , p ≥ 1$ and any $x , y ∈ [ 0 , 1 ]$, the generator is $f t ( x ) = 1 − x p$.
For the s-norm $x • s y = min { 1 , ( x p + y p ) 1 / p } , p ≥ 1$ and any $x , y ∈ [ 0 , 1 ]$, the generator is $f s ( x ) = x p$.
Theorem 3.
Let $f t , f s$ be generators of the triangular norms $• t , • s$. Then there exist operations $• p : [ 0 , 1 ] × [ 0 , 1 ] → [ 0 , 1 ] , • l : [ 0 , 1 ] × [ 0 , 1 ] → [ 0 , 1 ]$ defined by formulas:
$λ • p x = f t − 1 [ λ f t ( x ) ] , for λ f t ( x ) ∈ [ 0 , 1 ] 0 , otherwise .$
$λ • l x = f s − 1 [ λ f s ( x ) ] , for λ f s ( x ) ∈ [ 0 , 1 ] 1 , otherwise .$
Proof of Theorem 3.
Because $f t$ is a strictly decreasing function, there is only one value $f t − 1 [ λ f t ( x ) ] ∈ [ 0 , 1 ]$, when $λ f t ( x ) ∈ [ 0 , f s ( 0 ) ]$.
It is noted that $λ • p x = d f f t − 1 [ λ f t ( x ) ]$, for $λ f t ( x ) ∈ [ 0 , f t ( 0 ) ]$, and $λ • p x = d f 0$ otherwise.
Similarly, we define the operation $• l$. □
Definition 2.
Operations $• p , • l$ specified in Theorem 3 are calledp-norm(with properties similar to the power functions) and thel-norm(with properties similar to the linear function), respectively, and the system $S Yager = 〈 [ 0 , 1 ] , • t , • s , • p , • l , 0 , 1 〉$ is called the Yager system of the triangular norms.
The following notation agreement is accepted:
$λ • p x = d f x λ ,$
$λ • l x = d f λ x .$
Fact 1.
If $x λ = f t − 1 [ λ f t ( x ) ]$, for $λ f t ( x ) ∈ [ 0 , f t ( 0 ) ]$, then $f t ( x λ ) = λ f t ( x )$.
If $λ x = f s − 1 [ λ f s ( x ) ]$, for $λ f s ( x ) ∈ [ 0 , f s ( 1 ) ]$, then $f s ( λ x ) = λ f s ( x )$.
Theorem 4.
In the system $S Yager = 〈 [ 0 , 1 ] , • t , • s , • p ,$$• l , 0 , 1 〉$ operations $• p , • l$ satisfy the following conditions (for any $x , y , λ , λ 1 , λ 2 ∈ [ 0 , 1 ]$):
$λ ( x • s y ) = λ x • s λ y ,$
$( x • t y ) λ = x λ • t y λ ,$
$( λ 1 + λ 2 ) x = λ 1 x • s λ 2 x ,$
$x λ 1 + λ 2 = x λ 1 • t x λ 2 .$
Proof of Theorem 4.
• For Equation (18): $λ ( x • s y ) = f s − 1 [ λ f s ( x • s y ) ] = f s − 1 [ λ f s ( x ) + λ f s ( y ) ] = f s − 1 [ f s ( λ x ) + f s ( λ y ) ] = λ x • s λ y$, for $f s ( x • s y ) ∈ [ 0 , 1 ]$, and since $λ f s ( x • s y ) ≤ f s ( x • s y )$, so $λ f s ( x • s y ) ∈ [ 0 , 1 ]$.
• For Equation (19): $( x • t y ) λ = f t − 1 [ λ f t ( x • t y ) ] = f t − 1 [ λ f t ( x ) + λ f t ( y ) ] = f t − 1 [ f t ( x λ ) + f t ( y λ ) ] = x λ • t y λ$, for $f t ( x • t y ) ∈ [ 0 , 1 ]$, and since $λ f t ( x • t y ) ≤ f t ( x • t y )$, so $λ f t ( x • t y ) ∈ [ 0 , 1 ]$.
• For Equation (20): $( λ 1 + λ 2 ) x = f s − 1 [ ( λ 1 + λ 2 ) f s ( x ) ] = f s − 1 [ λ 1 f s ( x ) + λ 2 f s ( x ) ] = f s − 1 [ f s ( λ 1 x ) + f s ( λ 2 x ) ] = λ 1 x • s λ 2 x$, for $( λ 1 + λ 2 ) f s ( x ) = f s ( λ 1 x ) + f s ( λ 2 x ) ∈ [ 0 , 1 ]$.
• For Equation (21): $x λ 1 + λ 2 = f t − 1 [ ( λ 1 + λ 2 ) f t ( x ) ] = f t − 1 [ λ 1 f t ( x ) + λ 2 f t ( x ) ] = f t − 1 [ f t ( x λ 1 ) + f t ( x λ 2 ) ] = x λ 1 • t x λ 2$, for $( λ 1 + λ 2 ) f t ( x ) = f t ( x λ 1 ) + f t ( x λ 2 ) ∈ [ 0 , 1 ]$.

## 3. n-Pythagorean Fuzzy Set and Yager Aggregation Operators

Definition 3.
Let F be a set of all fuzzy sets for the nonempty space X. Any function $p : X → [ 0 , 1 ] × [ 0 , 1 ]$ defined for any $μ p , v p ∈ F$ is:
$p = { 〈 x , 〈 μ p ( x ) , v p ( x ) 〉 〉 : x ∈ X } .$
It is called then-Pythagorean fuzzy set(n-PFS) if the following condition is satisfied (for any natural number $n > 0$ ):
$0 ≤ ( μ p ( x ) ) n + ( v p ( x ) ) n ≤ 1 , for any x ∈ X .$
Let n-PFS mean set of all n-PFS.
The fuzzy sets $μ p , v p$ indicate the membership and non-membership functions. Zhang and Xu  considered $p ( x ) = 〈 μ p ( x ) , v p ( x ) 〉$ as n-Pythagorean fuzzy number (n-PFN) represented by $p = 〈 μ p , v p 〉$. The notation is used:
$n - PFN = d f { 〈 μ , v 〉 ∈ [ 0 , 1 ] × [ 0 , 1 ] : 0 ≤ μ n + v n ≤ 1 } .$
Fact 2.
$n - PFN = { p ( x ) : x ∈ X , p ∈ n - PFS } .$
When $n = 1$, then the 1-Pythagorean fuzzy sets are the intuitionistic fuzzy sets (IFS), which were studied by Atanassow . Moreover, when $n = 2$, then the 2-Pythagorean fuzzy sets are the PFS of Yager .
Simple arithmetic properties of inequalities $0 ≤ μ n + 1 + v n + 1 ≤ μ n + v n ≤ 1$ result from:
Theorem 5.
For any natural number $n > 1$
$n - PFN ⊆ ( n + 1 ) - PFN ⊆ [ 0 , 1 ] × [ 0 , 1 ] .$
Thus, entering a power scale for a value of the membership and non-membership functions allows to replace $〈 μ , v 〉 ∈ [ 0 , 1 ] × [ 0 , 1 ]$ such that $μ + v > 1$, by $〈 μ n , v n 〉 ∈ 1 - PFN$, for some n. As a result, the aggregation operations on the IFS can be extended to the aggregation operations on the n-PFS.
Theorem 6.
In any system $S Yager = 〈 [ 0 , 1 ] , • t , • s , • p ,$$• l , 0 , 1 〉$, for any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ 1 - PFN$ and a number $λ ∈ [ 0 , 1 ]$, the following conditions are satisfied:
$〈 μ 1 • s μ 2 , v 1 • t v 2 〉 ∈ 1 - PFN ,$
$〈 μ 1 • t μ 2 , v 1 • s v 2 〉 ∈ 1 - PFN ,$
Furthermore, in some systems $S Yager$ (not in all - see Proof of Theorem 3,4 and Remark 1) there are additional conditions:
$〈 λ • l μ 1 , λ • p v 1 〉 ∈ 1 - PFN ,$
$〈 λ • p μ 1 , λ • l v 1 〉 ∈ 1 - PFN .$
Proof of Theorem 6.
• For Equation (27): $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ 1 - PFN$ iff $μ 1 + v 1 ≤ 1 , μ 2 + v 2 ≤ 1$ if and only if $μ 1 ≤ 1 − v 1 , μ 2 ≤ 1 − v 2$.
Hence and from the monotonicity of the s-norm and its determination by t-norm:
$μ 1 • s μ 2 ≤ ( 1 − v 1 ) • s ( 1 − v 2 ) = 1 − ( 1 − ( 1 − v 1 ) • s ( 1 − v 2 ) = 1 − v 1 • t v 2$ iff $μ 1 • s μ 2 + v 1 • t v 2 ≤ 1$ iff $〈 μ 1 • s μ 2 , v 1 • t v 2 〉 ∈ 1 - PFN$.
• For Equation (28): $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ 1 - PFN$ iff $〈 v 1 , μ 1 〉 , 〈 v 2 , μ 2 〉 ∈ 1 - PFN$.
Hence, and from point 1, there is $〈 v 1 • s v 2 , μ 1 • t μ 2 〉 ∈ 1 - PFN$, which is equivalent to $〈 μ 1 • t μ 2 , v 1 • s v 2 〉 ∈ 1 - PFN$.
• For Equation (29): let $μ • s v = max { μ , v } , μ • t v = min { μ , v }$, then $f s ( x ) = x , f t ( x ) = 1 ˘ x$ (see Example 1);
$〈 μ 1 , v 1 〉 ∈ 1 - PFN$ iff $μ 1 + v 1 ≤ 1$;
$λ • l μ 1 = f s − 1 [ λ f s ( μ 1 ) ] = λ μ 1$ and $λ • p v 1 = f s − 1 [ λ f s ( v 1 ) ] = 1 − λ ( 1 − v 1 )$; $λ • l μ 1 + λ • p v 1 = λ μ 1 + 1 − λ ( 1 − v 1 ) = 1 − λ + λ ( μ 1 + v 1 ) ;$
Since $λ ( μ 1 + v 1 ) ≤ λ$, so $0 ≤ 1 − λ + λ ( μ 1 + v 1 ) ≤ 1$.
• For Equation (30): let $μ • s v = max { μ , v } , μ • t v = min { μ , v }$, then $f s ( x ) = x , f t ( x ) = 1 ˘ x$;
$〈 μ 1 , v 1 〉 ∈ 1 - PFN$ iff $μ 1 + v 1 ≤ 1$ iff $〈 v 1 , μ 1 〉 ∈ 1 - PFN$.
Hence, and from point 3, there is $〈 λ • l v 1 , λ • p μ 1 〉 ∈ 1 - PFN$, which is equivalent to $〈 λ • p μ 1 , λ • l v 1 〉 ∈ 1 - PFN$.
Remark 1.
Assuming generators of triangular norms from the Example 2 $λ • l μ 1 = λ 1 / p μ 1 , λ • p v 1 = 1 − λ 1 / p ( 1 − v 1 )$, for $μ 1 = 1 / 2 , v 1 = 7 / 8 , λ = 1 / 4$ and $p = 2$, it is obtained that $〈 λ • l μ 1 , λ • p v 1 〉 = 〈 1 / 8 , 15 / 16 〉 ∉ 1 - PFN , ( 1 < 1 / 8 + 15 / 16 )$.
Theorem 7.
Let the system $S Yager = 〈 [ 0 , 1 ] , • t ,$$• s , • p ,$$• l , 0 , 1 〉$ conditions from Equations (27)–(30) of the Theorem 6 apply. Then, for any natural number $n > 1$, for any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ n - PFN$, and number $λ ∈ [ 0 , 1 ]$ the following conditions are satisfied:
$〈 ( μ 1 n • s μ 2 n ) 1 / n , ( v 1 n • t v 2 n ) 1 / n 〉 ∈ n - PFN ,$
$〈 ( μ 1 n • t μ 2 n ) 1 / n , ( v 1 n • s v 2 n ) 1 / n 〉 ∈ n - PFN ,$
$〈 ( λ • l μ 1 n ) 1 / n , ( λ • p v 1 n ) 1 / n 〉 ∈ n - PFN ,$
$〈 ( λ • p μ 1 n ) 1 / n , ( λ • l v 1 n ) 1 / n 〉 ∈ n - PFN .$
Proof of Theorem 7.
$〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ n - PFN iff 〈 μ 1 n , v 1 n 〉 , 〈 μ 2 n , v 2 n 〉 ∈ 1 - PFN .$
Then, the conditions of Theorem 6 are satisfied, which are equivalent to the above conditions (31)–(34). □
Definition 4.
In the system $S Yager = 〈 [ 0 , 1 ] , • t , • s , • p ,$$• l , 0 , 1 〉$, the following aggregation operators are defined: theYager operators on n-PFN: for any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ n - PFN$ and number $λ ∈ [ 0 , 1 ]$.
When conditions (27)–(30) of the Theorem 6 are satisfied:
$〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 = 〈 ( μ 1 n • s μ 2 n ) 1 / n , ( v 1 n • t v 2 n ) 1 / n 〉 ,$
$〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 = 〈 ( μ 1 n • t μ 2 n ) 1 / n , ( v 1 n • s v 2 n ) 1 / n 〉 ,$
$λ 〈 μ 1 , v 1 〉 = 〈 ( λ • l μ 1 n ) 1 / n , ( λ • p v 1 n ) 1 / n 〉 ,$
$〈 μ 1 , v 1 〉 λ = 〈 ( λ • p μ 1 n ) 1 / n , ( λ • l v 1 n ) 1 / n 〉 .$
when $〈 ( λ • l μ 1 n ) 1 / n , ( λ • p v 1 n ) 1 / n 〉 ∉ n - PFN$, then:
$λ 〈 μ 1 , v 1 〉 = 〈 1 , 0 〉 ,$
or when $〈 ( λ • p μ 1 n ) 1 / n , ( λ • l v 1 n ) 1 / n 〉 ∉ n - PFN$, then:
$〈 μ 1 , v 1 〉 λ = 〈 0 , 1 〉 .$
Hence, in any system $S Yager = 〈 [ 0 , 1 ] , • t , • s , • p , • l , 0 , 1 〉$, using the Theorem 4, there is:
Theorem 8.
For any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 , 〈 μ 3 , v 3 〉 ∈ n - PFN$ and number $λ ∈ [ 0 , 1 ]$:
$〈 μ 1 , v 1 〉 ⊕ 〈 0 , 1 〉 = 〈 μ 1 , v 1 〉 , 〈 μ 1 , v 1 〉 ⊕ 〈 1 , 0 〉 = 〈 1 , 0 〉 ,$
$〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 = 〈 μ 2 , v 2 〉 ⊕ 〈 μ 1 , v 1 〉 ,$
$( 〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 ) ⊕ 〈 μ 3 , v 3 〉 = 〈 μ 1 , v 1 〉 ⊕ ( 〈 μ 2 , v 2 〉 ⊕ 〈 μ 3 , v 3 〉 ) ,$
$〈 μ 1 , v 1 〉 ⊕ 〈 1 , 0 〉 = 〈 μ 1 , v 1 〉 , 〈 μ 1 , v 1 〉 ⊗ 〈 0 , 1 〉 = 〈 0 , 1 〉 ,$
$〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 = 〈 μ 2 , v 2 〉 ⊕ 〈 μ 1 , v 1 〉 ,$
$( 〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 ) ⊕ 〈 μ 3 , v 3 〉 = 〈 μ 1 , v 1 〉 ⊕ ( 〈 μ 2 , v 2 〉 ⊕ 〈 μ 3 , v 3 〉 ) ,$
$λ ( 〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 ) = λ 〈 μ 1 , v 1 〉 ⊕ λ 〈 μ 2 , v 2 〉 ,$
$( 〈 μ 1 , v 1 〉 ⊕ 〈 μ 2 , v 2 〉 ) λ = 〈 μ 1 , v 1 〉 λ ⊕ 〈 μ 2 , v 2 〉 λ ,$
$( λ 1 + λ 2 ) 〈 μ 1 , v 1 〉 = λ 1 〈 μ 1 , v 1 〉 ⊕ λ 2 〈 μ 1 , v 1 〉 ,$
$〈 μ 1 , v 1 〉 λ 1 + λ 2 = 〈 μ 1 , v 1 〉 λ 1 ⊕ 〈 μ 1 , v 1 〉 λ 2 .$

## 4. Triangular Norms in the n-PFN and the n-PFS Algebra

Definition 5.
For any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 ∈ n - PFN$:
$〈 μ 1 , v 1 〉 ≤ n 〈 μ 2 , v 2 〉 iff μ 1 ≤ μ 2 , v 1 ≥ v 2 .$
The results of operations maximum and minimum for any $A ⊆ n - PFN$ are described for the relation $≤ n$ and are denoted by: $max n A , min n A$.
Fact 3.
For any $x , y ∈ [ 0 , 1 ]$:
1.
$〈 0 , 1 〉 ≤ n 〈 0 , x 〉 ≤ n 〈 0 , 0 〉 ≤ n 〈 y , 0 〉 ≤ n 〈 1 , 0 〉 ,$
2.
$〈 0 , 1 〉 ≤ n 〈 x , y 〉 ≤ n 〈 1 , 0 〉$, when $〈 x , y 〉 ∈ n - PFN .$
3.
$〈 0 , 1 〉 = min n n - PFN , 〈 1 , 0 〉 = max n n - PFN .$
Fact 4.
There is:
$n - PFN = { 〈 x , y 〉 ∈ [ 0 , 1 ] × [ 0 , 1 ] : 〈 0 , 1 〉 ≤ n 〈 x , y 〉 ≤ n 〈 1 , 0 〉 } .$
Definition 6.
There are:
1.
The operation $∘ t : n - PFN × n - PFN → n - PFN$ is called at-norm in the set n-PFNordered by the relations $≤ n$, when for any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 , 〈 μ 3 , v 3 〉 ∈ n - PFN$:
(a)
boundary conditions
$〈 0 , 1 〉 ∘ t 〈 μ 1 , v 1 〉 = 〈 0 , 1 〉 , 〈 μ 1 , v 1 〉 ∘ t 〈 1 , 0 〉 = 〈 μ 1 , v 1 〉 ,$
(b)
monotonicity
$〈 μ 1 , v 1 〉 ∘ t 〈 μ 2 , v 2 〉 ≤ n 〈 μ 3 , v 3 〉 ∘ t 〈 μ 2 , v 2 〉 , w h e n 〈 μ 1 , v 1 〉 ≤ n 〈 μ 3 , v 3 〉 ,$
(c)
commutativity
$〈 μ 1 , v 1 〉 ∘ t 〈 μ 2 , v 2 〉 = 〈 μ 2 , v 2 〉 ∘ t 〈 μ 1 , v 1 〉 ,$
(d)
associativity
$〈 μ 1 , v 1 〉 ∘ t ( 〈 μ 2 , v 2 〉 ∘ t 〈 μ 3 , v 3 〉 ) = ( 〈 μ 1 , v 1 〉 ∘ t 〈 μ 2 , v 2 〉 ) ∘ t 〈 μ 3 , v 3 〉 .$
2.
The operation $∘ s : n - PFN × n - PFN → n - PFN$ is called thes-norm in the set n-PFNordered by the relations $≤ n$, when for any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 , 〈 μ 3 , v 3 〉 ∈ n - PFN$:
(a)
boundary conditions
$〈 1 , 0 〉 ∘ s 〈 μ 1 , v 1 〉 = 〈 1 , 0 〉 , 〈 μ 1 , v 1 〉 ∘ s 〈 0 , 1 〉 = 〈 μ 1 , v 1 〉 ,$
(b)
monotonicity
$〈 μ 1 , v 1 〉 ∘ s 〈 μ 2 , v 2 〉 ≤ n 〈 μ 3 , v 3 〉 ∘ s 〈 μ 2 , v 2 〉 , w h e n 〈 μ 1 , v 1 〉 ≤ n 〈 μ 3 , v 3 〉 ,$
(c)
commutativity
$〈 μ 1 , v 1 〉 ∘ s 〈 μ 2 , v 2 〉 = 〈 μ 2 , v 2 〉 ∘ s 〈 μ 1 , v 1 〉 ,$
(d)
associativity
$〈 μ 1 , v 1 〉 ∘ s ( 〈 μ 2 , v 2 〉 ∘ s 〈 μ 3 , v 3 〉 ) = ( 〈 μ 1 , v 1 〉 ∘ s 〈 μ 2 , v 2 〉 ) ∘ s 〈 μ 3 , v 3 〉 .$
Theorem 9.
The Yager operatoron the $n - PFN$ is a t-norm in the set $n - PFN$ and the operatoris a s-norm in the set $n - PFN$.
Proof of Theorem 9.
Conditions (45)–(47) of the Theorem 8 proof that the operator ⊗ satisfies conditions (a),(c), and (d) of the Definition 6 (1) of the t-norm in the set $n - PFN$. It is enough to prove that this operation is monotonous.
For any $〈 μ 1 , v 1 〉 , 〈 μ 2 , v 2 〉 , 〈 μ 3 , v 3 〉 ∈ n - PFN$
$〈 μ 1 , v 1 〉 ⊗ 〈 μ 2 , v 2 〉 = 〈 ( μ 1 n • t μ 2 n ) 1 / n , ( v 1 n • s v 2 n ) 1 / n 〉$,
$〈 μ 3 , v 3 〉 ⊗ 〈 μ 2 , v 2 〉 = 〈 ( μ 3 n • t μ 2 n ) 1 / n , ( v 3 n • s v 2 n ) 1 / n 〉 .$
Let $〈 μ 1 , v 1 〉 ≤ n 〈 μ 3 , v 3 〉$. Then $μ 1 ≤ μ 3 , v 1 ≥ v 3$. Hence, and from the monotonicity of the t-norm and s-norm, it is obtained that:
$μ 1 n • t μ 2 n ≤ μ 3 n • t μ 2 n$ and $v 3 n • s v 2 n ≤ v 1 n • s v 2 n$ iff
$( μ 1 n • t μ 2 n ) 1 / n ≤ ( μ 3 n • t μ 2 n ) 1 / n$ and $( v 1 n • s v 2 n ) 1 / n ≥ ( v 3 n • s v 2 n ) 1 / n$ iff
$〈 ( μ 1 n • t μ 2 n ) 1 / n , ( v 1 n • s v 2 n ) 1 / n 〉 ≤ n 〈 ( μ 3 n • t μ 2 n ) 1 / n , ( v 3 n • s v 2 n ) 1 / n 〉$ iff
$〈 μ 1 , v 1 〉 ⊗ 〈 μ 2 , v 2 〉 ≤ n 〈 μ 3 , v 3 〉 ⊗ 〈 μ 2 , v 2 〉 .$
Proof that the operator ⊕ satisfies conditions of the Definition 6 (2) about the s-norm in the set $n - PFN$ is analogical. □
Summarizing, for the knowledge of operations and relationships introduced in the $n - PFN$, the following operations and conclusion relationships can be determined for the $n - PFS$:
Definition 7.
For any $p 1 , p 2 ∈ n - PFS$, and number $λ ∈ [ 0 , 1 ]$:
$p 1 ⊕ p 2 = { 〈 x , 〈 μ p 1 ( x ) , v p 1 ( x ) 〉 ⊕ 〈 μ p 2 ( x ) , v p 2 ( x ) 〉 〉 : x ∈ X } ,$
$p 1 ⊗ p 2 = { 〈 x , 〈 μ p 1 ( x ) , v p 1 ( x ) 〉 ⊗ 〈 μ p 2 ( x ) , v p 2 ( x ) 〉 〉 : x ∈ X } ,$
$λ p 1 = { 〈 x , λ 〈 μ p 1 ( x ) , v p 1 ( x ) 〉 〉 : x ∈ X } ,$
$p 1 λ = { 〈 x , 〈 μ p 1 ( x ) , v p 1 ( x ) 〉 λ 〉 : x ∈ X } ,$
$supp ( p 1 ) = { x ∈ X : μ p 1 ( x ) > 0 , v p 1 ( x ) > 0 } ,$
$p 1 ⊆ n p 2 iff for any x ∈ X , 〈 μ p 1 ( x ) , v p 1 ( x ) 〉 ≤ n 〈 μ p 2 ( x ) , v p 2 ( x ) 〉 .$
The system n-PFS, with defined in the Definition 7 operations (t-norm, s-norm, p-norm, l-norm, and support) and inclusion relations, is called the n-PFS algebra.
Let $1 = d f 〈 0 , 1 〉 , 0 = d f 〈 1 , 0 〉$. Then from the Definition 7 and the Theorem 8 there are:
Theorem 10.
In the algebra n-PFS, for any $p 1 , p 2 , p 3 ∈ n - PFN$ and the number $λ ∈ [ 0 , 1 ]$:
$p 1 ⊕ 0 = p 1 , p 1 ⊕ 1 = 1 ,$
$p 1 ⊕ p 2 = p 2 ⊕ p 1 ,$
$( p 1 ⊕ p 2 ) ⊕ p 3 = p 1 ⊕ ( p 2 ⊕ p 3 ) ,$
$p 1 ⊗ 1 = p 1 , p 1 ⊗ 0 = 0 ,$
$p 1 ⊗ p 2 = p 2 ⊗ p 1 ,$
$( p 1 ⊗ p 2 ) ⊗ p 3 = p 1 ⊗ ( p 2 ⊗ p 3 ) ,$
$λ ( p 1 ⊕ p 2 ) = λ p 1 ⊕ λ p 2 ,$
$( p 1 ⊗ p 2 ) λ = p 1 λ ⊗ p 2 λ ,$
$( λ 1 + λ 2 ) p 1 = λ 1 p 1 ⊕ λ 2 p 1 ,$
$p 1 λ 1 + λ 2 = p 1 λ 1 ⊗ p 1 λ 2 .$

## 5. Conclusions

This paper presents the elements of deductive theory of the n-PFS, where the membership degree $μ$ and the non-membership degree v determine not only in the square scale, but in any power scale, i.e., $0 ≤ μ n + v n ≤ 1$. As a result, any local deductions in the n-PFS range can be formulated. It may be interesting to use the described model to create similar models but based on other functional scales, for example for the function of scale $f n ( x ) = x / n : 0 ≤ μ / n + v / n ≤ 1$ or $f n ( x ) = 1 + log n ( x + 1 )$, for $x ∈ [ 0 , 1 ]$, where $f ( x ) < x : 0 ≤ ( l + log n ( μ + 1 ) ) + ( 1 + log n ( v + 1 ) ) ≤ 1$. In the research, the n-PFS theory can be used to describe n-PFS as a system of information granules .

## Funding

This research received no external funding.

## Conflicts of Interest

The author declares no conflict of interest.

## References

1. Zadeh, L.A. Fuzzy sets. Inf. Control 1965, 8, 338–353. [Google Scholar] [CrossRef][Green Version]
2. Atanassov, K.T. Intuitionistic fuzzy sets. Fuzzy Sets Syst. 1986, 20, 87–96. [Google Scholar] [CrossRef]
3. Atanassov, K.T. Intuitionistic Fuzzy Sets; Springer: Berlin/Heidelberg, Germany, 1999. [Google Scholar]
4. Yager, R.R. Pythagorean fuzzy subsets. In Proceedings of the 2013 Joint IFSAWorld Congress and NAFIPS Annual Meeting (IFSA/NAFIPS), Edmonton, AB, Canada, 24–28 June 2013; pp. 57–61. [Google Scholar]
5. Yager, R.R. Pythagorean membership grades in multicriteria decision making. IEEE Trans. Fuzzy Syst. 2014, 22, 958–965. [Google Scholar] [CrossRef]
6. Zhang, X.; Xu, Z. Extension of TOPSIS to multiple criteria decision making with Pythagorean fuzzy sets. Int. J. Intell. Syst. 2014, 29, 1061–1078. [Google Scholar] [CrossRef]
7. Garg, H. A novel correlation coefficients between Pythagorean fuzzy sets and its applications to decisionmaking processes. Int. J. Intell. Syst. 2016, 31, 1234–1252. [Google Scholar] [CrossRef]
8. Garg, H. Confidence levels based Pythagorean fuzzy aggregation operators and its application to decisionmaking process. Comput. Math. Organ. Theory 2017, 23, 546–571. [Google Scholar] [CrossRef]
9. Atanassov, K.T. On the Modal Operators Defined Over The Intuitionistic fuzzy Sets. Notes Intuit. Fuzzy Sets 2004, 10, 7–12. [Google Scholar]
10. Atanassov, K.T. On Intuitionistic Fuzzy Sets Theory; Springer: Berlin/Heidelberg, Germany, 2012. [Google Scholar]
11. Dencheva, K. Extension of intuitionistic fuzzy modal operators ⊗ and ⊕. Proc. Second Int. IEEE Symp. Intell. syst. 2004, 3, 21–22. [Google Scholar]
12. Yılmaz, S.; Bal, A. Extentsion of intuitionistic fuzzy modal operators diagram with new operators. Notes Intuit. Fuzzy Sets 2014, 20, 26–35. [Google Scholar]
13. Akram, M.; Garg, H.; Ilyas, F. Multi-criteria group decision making based on ELECTRE I method in Pythagorean fuzzy information. Soft Comput. 2019, 24, 3425–3453. [Google Scholar] [CrossRef]
14. Akram, M.; Dudek, W.A.; Dar, J.M. Pythagorean Dombi fuzzy aggregation operators with application in multicriteria decision-making. Int. J. Intell. Syst. 2019, 34, 3000–3019. [Google Scholar] [CrossRef]
15. Akram, M.; Dudek, W.A.; Ilyas, F. Group decision-making based on Pythagorean fuzzy TOPSIS method. Int. J. Intell. Syst. 2019, 34, 1455–1475. [Google Scholar] [CrossRef]
16. Shahzadi, G.; Akram, M.; Al-KenaniInt, A.N. Decision-Making Approach under Pythagorean Fuzzy Yager Weighted Operators. Mathematics 2020, 8, 70. [Google Scholar] [CrossRef][Green Version]
17. Yager, R.R. Aggregation operators and fuzzy systems modeling. Fuzzy Sets Syst. 1994, 67, 129–145. [Google Scholar] [CrossRef]
18. Aczel, J. Lectures on Functional Equations and Their Applications; Academic Press: New York, NY, USA, 1966. [Google Scholar]
19. Bryniarska, A. Certain information granule system as a result of sets approximation by fuzzy context. Int. J. Approx. Reason. 2019, 111, 1–20. [Google Scholar] [CrossRef]
 Publisher’s Note: MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.

## Share and Cite

MDPI and ACS Style

Bryniarska, A. The n-Pythagorean Fuzzy Sets. Symmetry 2020, 12, 1772. https://doi.org/10.3390/sym12111772

AMA Style

Bryniarska A. The n-Pythagorean Fuzzy Sets. Symmetry. 2020; 12(11):1772. https://doi.org/10.3390/sym12111772

Chicago/Turabian Style

Bryniarska, Anna. 2020. "The n-Pythagorean Fuzzy Sets" Symmetry 12, no. 11: 1772. https://doi.org/10.3390/sym12111772

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.